Electrospun Nanofibers for Tissue Engineering (Journal of Fiber Bioengineering and Informatics, 2013)
Electrospun nanofibers have increasingly attracted attention to be used as new generation tissueengineering scaffolds since they have the nanofibrous structure, which can biomimic the nativeExtracellular Matrix (ECM). This paper gives the review of our 10 years research on electrospunnanofibers for tissue engineering. Natural polymers like collagen and chitosan have been electrospun intocomplex nanofibers to biomimic the native ECM both in structure and components. Collagen-chitosanor silk fibroin (SF) was also blended with synthetic poly (L-lactide-co-ε-caprolactone) (P(LLA-CL)) andelectrospun into collgen-chitosan-P (LLA-CL) nanofibers or SF-P(LLA-CL) nanofibers to achieve bothgood mechanical properties and biocompatibility. Coaxial electrospinning was used to encapsulate thebiomolecules into nanofibers to display antithrombotic properties. The nanofiber scaffolds have beenused for skin, nerve and blood vessel tissue engineering in vivo.
Keywords: Nanofiber; Electrospinning; Tissue Engineering; P (LLA-CL); Scaffolds